Inovasi Penerapan Teknologi pada Proses Pengolahan Limbah Minyak Jelantah Menjadi Sabun Padatan di Desa Tualang Teungoh Kota Langsa: Innovation of the Application of Technology to the Processing of Used Cooking Oil into Solid Soap in Tualang Teungoh Village, Langsa City - Rahmawati, Rahmawati; Halimatussakdiah, Halimatussakdiah; Purwandito, Meilandy; Purba, Herlina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Community Service Activities (PKM) have been completed to solve community problems through innovation regarding the use of used cooking oil waste as raw material for solid soap. The targets of this service activity are the people of Tualang Teungoh Village, Langsa City, Aceh, especially PKK women. The problem faced by partners is the accumulation of used cooking oil waste that cannot be utilized. Through this service activity, the community will be educated to utilize science and technology to utilize used cooking oil waste as raw material for making multi-purpose solid soap. The series of activities that will be carried out in the Service include several stages, first an initial survey is carried out regarding the problems faced by the village community, next is outreach activities, and then practical training in making multipurpose solid soap, the final stage is monitoring partners in the solid soap packaging process. A product has been obtained in the form of multi-purpose solid soap from used cooking waste which can be used for washing household equipment in everyday life. This product is expected to become one of the local products that has market opportunities thereby increasing the utilization of household waste and improving the economic level of the community.